A systematic dry etching process for profile control of quantum dots and nanoconstrictions - Madnarski, Sutikno; Uda, Hashim; Zul Azhar, Zahid Jamal (Elsevier B.V., 2009)
Link to publisher's homepage at www.elsevier.com